Comparative removal of Suwannee River natural organic matter and perfluoroalkyl acids by anion exchange: Impact of polymer composition and mobile counterion. (1st July 2020) - Laura del Moral, Lerys; Choi, Youn Jeong; Boyer, Treavor H.
Abstract: Anion exchange resin (AER) adsorption is an established technology for water treatment and groundwater remediation. Two contaminants amenable to AER treatment are natural organic matter (NOM) and per- and polyfluoroalkyl substances (PFAS), specifically anionic perfluoroalkyl acids (PFAAs) such as perfluorooctanoate (PFOA) and perfluorooctane sulfonate (PFOS). NOM is ubiquitous in natural waters and is often targeted for removal. PFAS occurrence in water resources is a human health concern. Accordingly, the goal of this research was to provide new insights on the use of AER for water treatment considering separate and combined removal of NOM and PFAAs. Batch experiments were conducted comparing polystyrene and polyacrylic AER in both chloride- and sulfate-forms using natural groundwater spiked with Suwannee River natural organic matter (SRNOM) and/or six PFAAs. The polymer composition of the AER had a significant impact on contaminant removal with polystyrene resin more effective for PFAA removal and polyacrylic resin more effective for SRNOM removal. Both resins had type I quaternary ammonium functional groups; however, the polyacrylic resin had trimethyl ammonium whereas the polystyrene resin had triethyl ammonium. Therefore, the influence of polymer composition could not be isolated conclusively from functional group chemistry. Polystyrene AER showed greater removal of PFAAs with sulfonate than carboxylate head group and 8-carbon than 4-carbon chain length. Removal of SRNOM and PFAAs by both resin polymer compositions were greater when sulfate was the mobile counterion ion than chloride. The results of this research have important implications for using AER for water treatment and remediation. Foremost, polymer composition and mobile counterion form of the resin can be selected to target specific contaminants and maximize contaminant removal. When contaminants have unique interactions with AER such as SRNOM and polyacrylic resin and PFAAs and polystyrene resin, the presence of one contaminant does not impact removal of the other contaminant. Highlights: Resin polymer, functional group, and initial counterion affects contaminant removal. Polystyrene resin was selective for perfluoroalkyl acids. Polyacrylic resin was selective for Suwannee River NOM. Changing resin counterion from chloride to sulfate increased contaminant removal.